Review of Economic Design - Kesten, Onur.; Yildirim, Huseyin; Meyer-ter-Vehn, Moritz; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Review of Economic Design comprises the creative art and science of inventing, analyzing and testing economic as well as social and political institutions and mechanisms aimed at achieving individual objectives and social goals. In this age of Economic Design, the accumulated traditions and wealth of knowledge in normative and positive economics and the strategic analysis of game theory are applied with novel ideas in the creative tasks of designing and assembling diverse legal-economic instruments. These include constitutions and other assignments of rights, mechanisms for allocation or regulation, tax and incentive schemes, contract forms, voting and other choice aggregation procedures, markets, auctions, organizational forms, such as partnerships, together with supporting membership and other property rights, and information systems. These designs, the methods of analysis used in their scrutiny, as well as the mathematical techniques and empirical knowledge they employ, along with comparative assessments of the performance of known economic systems and implemented designs, all of these form natural components of the subject matter of Economic Design. Officially cited as: Rev Econ Design.
Keywords: Game theory; Economics; Management science; Economic theory; Microeconomics; Economics, general; Economic Theory/Quantitative Economics/Mathematical Methods; Game Theory, Economics, Social and Behav. Sciences; Microeconomics; Behavioral/Experimental Economics